If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3x + 3 = 0 Reorder the terms: 3 + 3x + 2y = 0 Solving 3 + 3x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 3x + -3 + 2y = 0 + -3 Reorder the terms: 3 + -3 + 3x + 2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3x + 2y = 0 + -3 3x + 2y = 0 + -3 Combine like terms: 0 + -3 = -3 3x + 2y = -3 Add '-2y' to each side of the equation. 3x + 2y + -2y = -3 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = -3 + -2y 3x = -3 + -2y Divide each side by '3'. x = -1 + -0.6666666667y Simplifying x = -1 + -0.6666666667y
| (y+30)+110=180 | | (1+m)x^2-3mx+(1-m)=0 | | 3y-1+y+37y=6y+40-4y | | 6(4x+9)-23(x+5)=x-63 | | 2x+1=x+63 | | 3x+10=3x-19 | | 5x+4=-8+3x+2x | | 3y-1+y+3y=6y+40-4y | | y=7x+8kx | | 18x+15=4x+29 | | 10-k=12-1 | | 4p=p+14 | | 8-3h=5h+2 | | 17x^2-16x-12=0 | | -2r-6=12-4r | | -4x-12x=80 | | -6+19x=19x-6 | | 24h-6g= | | x+(x-35)=83 | | 9(x+2)=9(x+14) | | 6x^2+22x-5=0 | | 2x-(-10)=-5 | | 50x=6x-40 | | x+1-1(-2)=x+3-(-x+1) | | 3(4x+3)+11(x+3)=-24x | | 17-2-y*2ify=-2 | | 20x=2500 | | y=5-8 | | 2(p+8)4= | | y=8-8 | | =4x-6x+7x | | 5r=240 |